Inducible knockout mutagenesis reveals compensatorymechanisms elicited by constitutive BK channeldeficiency in overactive murine bladder - Sproßmann, Franz; Pankert, Patrick; Sausbier, Ulrike; Wirth, Angela; Zhou, Xiao-Bo; Madlung, Johannes; Zhao, Hong; Bucurenciu, Iancu; Jakob, Andreas; Lamkemeyer, Tobias; Neuhuber, Winfried; Offermanns, Stefan; et al. (The FEBS journal, 2009)
The large-conductance, voltage-dependent and Ca2+-dependent K+ (BK) channel links membrane depolarization and local increases in cytosolic free Ca2+ to hyperpolarizing K+ outward currents, thereby controlling smooth muscle contractility. Constitutive deletion of the BK channel in mice (BK−/−) leads to an overactive bladder associated with increased intravesical pressure and frequent micturition, which has been revealed to be a result of detrusor muscle hyperexcitability. Interestingly, time-dependent and smooth muscle-specific deletion of the BK channel (SM-BK−/−) caused a more severe phenotype than displayed by constitutive BK−/− mice, suggesting that compensatory pathways are active in the latter. In detrusor muscle of BK−/− but not SM-BK−/− mice, we found reduced L-type Ca2+ current density and increased expression of cAMP kinase (protein kinase A; PKA), as compared with control mice. Increased expression of PKA in BK−/− mice was accompanied by enhanced β-adrenoceptor/cAMP-mediated suppression of contractions by isoproterenol. This effect was attenuated by about 60-70% in SM-BK−/− mice. However, the Rp isomer of adenosine-3′,5′-cyclic monophosphorothioate, a blocker of PKA, only partially inhibited enhanced cAMP signaling in BK−/− detrusor muscle, suggesting the existence of additional compensatory pathways. To this end, proteome analysis of BK−/− urinary bladder tissue was performed, and revealed additional compensatory regulated proteins. Thus, constitutive and inducible deletion of BK channel activity unmasks compensatory mechanisms that are relevant for urinary bladder relaxation.